Divergent Paths to Moderation: Muhammadiyah, Nahdlatul Ulama, and the Construction of Wasatiyyah in Contemporary Indonesia - Saidul Amin; Fakhri, Abrar; Rahim, Adibah Binti Abdul; Fuad, Evans; Hardivizon, Hardivizon (Jurnal Studi Islam dan Kemuhammadiyahan (JASIKA), 2026)
Despite extensive scholarship on Islamic moderation in Indonesia, existing studies have not systematically explained why debates about wasatiyyah persist among actors who share fundamental moderate commitments. This study examines how Muhammadiyah and Nahdlatul Ulama (NU) Indonesia's two largest Islamic organizations construct competing visions of wasatiyyah through Islam Berkemajuan (Progressive Islam) and Islam Nusantara (Archipelagic Islam). Drawing on Gallie's essentially contested concepts, Bourdieu's field theory, and social movement framing theory, the study employs a qualitative comparative case study based on document analysis of official organizational sources from 2015 to 2024. The analysis across four challenges digital radicalism, transnational Islamic movements, state religious moderation policy, and internal diversity reveals that while both organizations share commitments to the Indonesian nation-state, Pancasila, and the rejection of violence, they articulate moderation through systematically different framings, state-positioning strategies, and institutional mechanisms shaped by distinct capital configurations. Muhammadiyah maintains critical distance from state power, emphasizing education-based responses, while NU pursues strategic partnership and mobilization-based approaches. The study demonstrates that wasatiyyah functions as an essentially contested concept whose meaning is constituted through ongoing organizational contestation. These findings contribute to debates on Islamic moderation by showing that the resilience of Indonesian Islam lies in its internal plurality rather than definitional uniformity, with implications for comparative studies in other Muslim-majority contexts